2019
DOI: 10.1186/s13099-019-0303-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of human norovirus GII genotypes detected in Ibaraki, Japan, during 2012–2018

Abstract: Background Human norovirus (HuNoV) is the major cause of viral acute gastroenteritis for all age groups in various countries. HuNoV GII in particular accounted for the majority of norovirus outbreaks, among which GII.4 caused repeated outbreaks for a long time. Besides GII.4, other norovirus genotypes, GII.2, GII.6, and GII.17, have also been prevalent in various contexts in recent years, but few detailed epidemiological studies of them have been performed and are poorly understood. We thus conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…In the phylogenetic tree, GII.1 clustered together with the genotypes from environmental samples ( Figure 2 ). This could be supported by Motoya et al's [ 56 ] speculation that both GI and GII strains can be detected in environmental samples.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the phylogenetic tree, GII.1 clustered together with the genotypes from environmental samples ( Figure 2 ). This could be supported by Motoya et al's [ 56 ] speculation that both GI and GII strains can be detected in environmental samples.…”
Section: Discussionmentioning
confidence: 60%
“…is could be supported by Motoya et al's [56] speculation that both GI and GII strains can be detected in environmental samples. (iv) GII.2 genotype reported in this study has been previously reported more common in hospitalised older children than in younger children [31,57,58].…”
Section: Discussionmentioning
confidence: 76%
“…Although noroviruses are antigenically and genetically diverse, a single genotype, i.e., GII.4, has been the predominant genotype globally. This genotype has been associated with not only sporadic gastroenteritis in children but also outbreaks in adults in various countries (Motoya et al, 2019;Wu et al, 2015;Polkowska et al, 2014;Medici et al, 2009). It was reported that the norovirus prevalence among hospitalized children was 18.5%, and that the most prevalent genotype in 2015 in Yogyakarta/West Nusa Tenggara, Indonesia was GII.4 Sydney[P31] (56%) (Nirwati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both assays have been shown to have broad specificity across genogroup II. However, genogroup II.2 (GII.2) has recently been reemerging as the cause of outbreaks in Japan and China [ 13 , 14 ]. For this purpose, a GII.2 strain, Snow Mountain, was selected as the target norovirus strain.…”
Section: Introductionmentioning
confidence: 99%